Cost-Minimization and Procedural Outcomes of Cold Snare Versus Cold Forceps Polypectomy for Small Colorectal Polyps: A Prospective Cohort Study Using Real Institutional Pricing - Güney Özkaya; İsmail Ege Subaşı; Sangar Abdullah; Sertaç Doğan; Şiva Nafez (Healthcare, 2026)
Background/Objectives: Although current guidelines (European Society of Gastrointestinal Endoscopy [ESGE] 2024, U.S. Multi-Society Task Force [USMSTF] 2020) recommend cold snare polypectomy (CSP) over cold forceps polypectomy (CFP) for small colorectal polyps, CFP remains widely used. Comparative economic data using real institutional pricing are scarce, limiting evidence for guideline-concordant resource allocation. We evaluated the healthcare economics and procedural outcomes of CSP versus CFP to assess their institutional resource implications. Methods: This prospective cohort study analyzed 153 consecutive patients (181 polyps ≤ 9 mm) at a single tertiary care center (June–October 2025). Technique allocation was based on endoscopist preference. The primary outcome was histopathologically confirmed complete resection; secondary outcomes were one-piece resection rate, procedure time, and cost outcomes based on institutional pricing. Firth penalized logistic regression, propensity score matching, and a neoplastic-restricted sensitivity analysis were performed. Results: Complete resection rates did not differ significantly (CSP 97.4% vs. CFP 94.2%, p = 0.29). CSP achieved higher one-piece resection rates (96.2% vs. 84.5%, p = 0.011) and shorter procedure time (median 3.2 vs. 5.1 min, p < 0.001). For 6–9 mm polyps, piecemeal resection was reduced with CSP (6.8% vs. 28.6%, p = 0.010). Despite higher device costs ($6 vs. $3), direct device-plus-labor cost was lower for CSP ($18.06 vs. $22.24, p < 0.001), with no statistically significant difference in complete resection. High-grade dysplasia was the only variable independently associated with incomplete resection. Findings were consistent in propensity score-matched (n = 61 pairs) and neoplastic-restricted (n = 134) analyses. Conclusions: By reducing direct device-plus-labor costs by 19% while improving one-piece resection, and remaining consistent across multivariable, propensity score-matched, and sensitivity analyses, these findings indicate that, within a cost-minimization framework, CSP is a cost-saving, guideline-concordant technique with no statistically significant difference in complete resection or observed adverse events.